The Social Construction of sub-Saharan Women’s Status through African Proverbs - Boahene, Lewis Asimeng (Mediterranean Journal of Social Sciences, 2013)
The continent of Africa, especially the sub-Saharan Africa, is known for its rich oral traditions and practices. Proverbs are themost widely used in this genre of oral arts and practices, and thus their influence is so strong to the point that even the conceptof social construction of women is so persistently carved from it. This paper examines how proverbs serve as storylinesbetween the ways proverbs represent the roles, statuses, and identity of women in traditional sub-Saharan Africa. The paperfocuses on the social construction and patriarchy as conceptsand uses critical discourse asa theoretical framework explainingthe status of women. The study also employed qualitative and the interpretive methods, which underscores the importance ofthe narratives on the lived experiences of the respondents.